Development of yourist destination recommendation prototype using case-based reasoning (CBR) approach / Siti Hafsah Sahak - Sahak, Siti Hafsah (2006)
This project will outline the creation of tourist destination recommendation prototype. Recommender systems became a significant tool in the field of tourism which offers an opportunity to find a travel bundle or a single travel item. The existing tourist recommendation systems have some shortcomings as they allow no or only very limited flexibility when taking constraints or preferences into user account. Therefore, case-based reasoning (CBR) approach has been proposed in this system for modeling and explaining human problem solving which has gaining popularity in recommender systems. This CBR technique is employed to support information search and choice processes that helps user to create a travel plan by recommending attractive travel products. It contained four specific processes which are retrieve, reuse, revise and retain that each of this process played important role to make solutions. As a result, by applying CBR approach in recommendation system, it enable users to browse a repository of past travels and make ranking possibly of the basic item such as activities provided when selected from catalogue which included in recommendation system other than make decisions on tourist destination that offered by this system. The advantages of this approach compared to rule-based are shown.